From Clinical Phenotype to Genotypic Modelling: Incidence and Prevalence of Recessive Dystrophic Epidermolysis Bullosa (RDEB) - Eichstadt S; Tang JY; Solis DC; Siprashvili Z; Marinkovich MP; Whitehead N; Schu M; Fang F; Erickson SW; Ritchey ME; Colao M; Spratt K; et al. (Dove Medical Press, 2019)
Shaundra Eichstadt,1 Jean Y Tang,1 Daniel C Solis,1 Zurab Siprashvili,1 M Peter Marinkovich,1,2 Nedra Whitehead,3 Matthew Schu,3 Fang Fang,3 Stephen W Erickson,3 Mary E Ritchey,3 Max Colao,4 Kaye Spratt,4 Amir Shaygan,5 Mark J Ahn,5 Kavita Y Sarin1 1Stanford University School of Medicine, Department of Dermatology, Redwood City, CA 94063, USA; 2Veterans Affairs Medical Center, Palo Alto, CA, USA; 3RTI International, Research Triangle Park, NC, USA; 4Abeona Therapeutics, New York, NY, USA; 5Department of Engineering and Technology Management, Portland State University, Portland, OR, USACorrespondence: Mark J AhnDepartment of Engineering and Technology Management, Portland State University, 1900 SW 4th Avenue, Suite LL50-01, Portland, OR 97201, USATel +1503961-4466Email mahn@pdx.eduBackground: Recessive dystrophic epidermolysis bullosa (RDEB) is an inherited genetic disorder characterized by recurrent and chronic open wounds with significant morbidity, impaired quality of life, and early mortality. RDEB patients demonstrate reduction or structural alteration type VII collagen (C7) owing to mutations in the gene COL7A1, the main component of anchoring fibrils (AF) necessary to maintain epidermal-dermal cohesion. While over 700 alterations in COL7A1 have been reported to cause dystrophic epidermolysis bullosa (DEB), which may be inherited in an autosomal dominant (DDEB) or autosomal recessive pattern (RDEB), the incidence and prevalence of RDEB is not well defined. To date, the widely estimated incidence (0.2–6.65 per million births) and prevalence (3.5–20.4 per million people) of RDEB has been primarily characterized by limited analyses of clinical databases or registries.Methods: Using a genetic modelling approach, we use whole exome and genome sequencing data to estimate the allele frequency of pathogenic variants. Through the ClinVar and NCBI database of human genome variants and phenotypes, DEB Register, and analyzing premature COL7A1 termination variants we built a model to predict the pathogenicity of previously unclassified variants. We applied the model to publicly available sequences from the Exome Aggregation Consortium (ExAC) and Genome Aggregation Database (gnomAD) and identified variants which were classified as pathogenic for RDEB from which we estimate disease incidence and prevalence.Results: Genetic modelling applied to the whole exome and genome sequencing data resulted in the identification of predicted RDEB pathogenic alleles, from which our estimate of the incidence of RDEB is 95 per million live births, 30 times the 3.05 per million live birth incidence estimated by the National Epidermolysis Bullosa Registry (NEBR). Using a simulation approach, we estimate a mean of approximately 3,850 patients in the US who may benefit from COL7A1-mediated treatments in the US.Conclusion: We conclude that genetic allele frequency estimation may enhance the underdiagnosis of rare genetic diseases generally, and RDEB specifically, which may improve incidence and prevalence estimates of patients who may benefit from treatment.Keywords: Dystrophic Epidermolysis Bullosa, genotype, phenotype, incidence, prevalence